GAMBARAN BERAT BADAN, KADAR HEMOGLOBIN, DAN KADAR HbCO PADA TIKUS GALUR WISTAR JANTAN ( Rattus Novergicus) YANG DIPAPAR ASAP ROKOK - Yuyun Erlina Susanti (STRADA : Jurnal Ilmiah Kesehatan, 2016)
Smoking is something that is habit for most Indonesian society, especially adult males. Smoking behavior of the population tends to increase. The exposure of cigarette smoke affects weight, binds Haemoglobin and produce CO bond in haemoglobin. The aim of this study was to analyze the difference of weight, Hemoglobin and Carboxyhemoglobin concentration in male Wistar rats. The study was a laboratory experimental design, using Post Test Control Group Design Research and RAL method (Complete Randomize Design). The sampel in this study were 10 male Wistar rats aged 3 months. The subjects were divided into 2 groups and each group received treatment for 28 days. Data of level HbCO was collected and analyzed by Anova One Way test at 95% confide nce level using SPSS version 16.0. The results showed significant difference in average Hb and HbCO concentration (p-value<0,05) male Wistar rats.The effect of cigarette smole exposured can lead to weight loss, a decrease in hemoglobin and increase Carboxyhemoglobin. Thus it is important area without cigarette smoke to avoid these impacts